2021
DOI: 10.1039/d0qo01609h
|View full text |Cite
|
Sign up to set email alerts
|

Hole-mediated photoredox catalysis: tris(p-substituted)biarylaminium radical cations as tunable, precomplexing and potent photooxidants

Abstract: Triarylamines are demonstrated as novel, tunable electroactivated photocatalysts that use dispersion precomplexation to harness the full potential of the visible photon (>4.0 V vs. SCE) in anti-Kasha photo(electro)chemical super-oxidations of arenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
135
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(156 citation statements)
references
References 94 publications
12
135
0
9
Order By: Relevance
“…The examples shown in Scheme 245 feature C-H substitution by azoles. 277 The formation of fluoroarene 904m from fluorobenzene shows that this is a highly powerful oxidising system for arenes and competitive with those discussed above [from the teams of Nicewicz and Lambert]. The best catalyst used in this transformation, TCBPA, was calculated to be a very strong oxidant (E red * = +4.19 V vs. SCE).…”
Section: Excitation Of Radical Cations and Radical Anions 9amentioning
confidence: 93%
“…The examples shown in Scheme 245 feature C-H substitution by azoles. 277 The formation of fluoroarene 904m from fluorobenzene shows that this is a highly powerful oxidising system for arenes and competitive with those discussed above [from the teams of Nicewicz and Lambert]. The best catalyst used in this transformation, TCBPA, was calculated to be a very strong oxidant (E red * = +4.19 V vs. SCE).…”
Section: Excitation Of Radical Cations and Radical Anions 9amentioning
confidence: 93%
“…An electrochemically generated radical ion implies replacing a stoichiometric amount of a sacrificial donor by a cathode, a situation that could be very advantageous having an easily tunable source of electrons. This was recognized by Lambert's and Wickens’ groups, among others who recently developed synthetic transformation s using radical anions and radical cations [16,17,33–35] …”
Section: Introductionmentioning
confidence: 96%
“…This was recognized by Lambert's and Wickens' groups, among others who recently developed synthetic transformations using radical anions and radical cations. [16,17,[33][34][35] In particular, Lambert and Lin et al [16] used dicyanoanthracene (DCA) as the catalyst to modify aryl chlorides performing borylation and CÀ H functionalization (Scheme 4). A photo-EC' mechanism was proposed for the formation of aryl radicals involving a key PET from the excited DCA * À to aryl halides, without detailed studies.…”
Section: Introductionmentioning
confidence: 99%
“…6 Despite these elegant advances, reductive e-PRC and biphotonic strategies 3 are still heavily focused on the reductions of aryl halides/pseudohalides through C(sp 2 )-X bond cleavages to generate aryl C(sp 2 ) radicals in an overall dehalogenation or functionalization with excesses of radical trapping agents. 5f,h Inspired by previous reports, 5 we envisioned that phosphinates of aliphatic alcohols (E p red = -2.2  -2.6 V vs. SCE) could undergo e-PRC reduction to give carbanions (Figure 1B). Thereby, an electroactivated-PhotoRedox Catalyst (e-PRCat) undergoes cathodic activation and photoexcitation to afford a potent reductant.…”
mentioning
confidence: 82%
“…4 Merging the advantages of these two important techniques has made photoelectrochemistry a tool for greener, more challenging and more selective molecular activations. 5 Pioneering reports by Xu, 5b-c,o Lambert, 5g,h,i,k Lin 5h,j and Wickens 5f have shown that introducing applied potential in photoredox catalysis is not only beneficial for accessing challenging redox reactions, but is also a green replacement for sacrificial redox additives. Among the various strategies for combining photocatalysis and electrochemistry 4a the sub-category coined electrochemically-mediated PhotoRedox Catalysis (e-PRC) is highly attractive.…”
mentioning
confidence: 99%